ANALISIS HUBUNGAN KAUSALITAS PENGANGGURAN, INFLASI DAN PERTUMBUHAN EKONOMI DI INDONESIA (DATA TIME SERIES 2010-2019) - Pakri Pakri (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
The purpose of this study is to determine the causal relationship between inflation and economic growth in Indonesia for the 2010-2019 period. The analytical method used in this study is quantitative using the VAR test with the Granger causality test method. The data collection technique used is secondary data obtained from the publication of the Indonesian Central Statistics Agency. Processing data in this study using the program views. The results show that there is a two-way causality relationship between movement and economic growth, then there is a one-way causality relationship between inflation and economic growth where only inflation affects economic growth, then there is a one-way causality relationship between inflation and inflation where only inflation has an effect. significant to economic growth.